Efficient generation of osteoclasts from human induced pluripotent stem cells and functional investigations of lethal CLCN7‐related osteopetrosis. (18th May 2021) - Rössler, Uta; Hennig, Anna Floriane; Stelzer, Nina; Bose, Shroddha; Kopp, Johannes; Søe, Kent; Cyganek, Lukas; Zifarelli, Giovanni; Ali, Salaheddine; von der Hagen, Maja; Strässler, Elisabeth Tamara; Hahn, Gabriele; et al.
ABSTRACT: Human induced pluripotent stem cells (hiPSCs) hold great potential for modeling human diseases and the development of innovative therapeutic approaches. Here, we report on a novel, simplified differentiation method for forming functional osteoclasts from hiPSCs. The three‐step protocol starts with embryoid body formation, followed by hematopoietic specification, and finally osteoclast differentiation. We observed continuous production of monocyte‐like cells over a period of up to 9 weeks, generating sufficient material for several osteoclast differentiations. The analysis of stage‐specific gene and surface marker expression proved mesodermal priming, the presence of monocyte‐like cells, and of terminally differentiated multinucleated osteoclasts, able to form resorption pits and trenches on bone and dentine in vitro. In comparison to peripheral blood mononuclear cell (PBMC)‐derived osteoclasts hiPSC‐derived osteoclasts were larger and contained a higher number of nuclei. Detailed functional studies on the resorption behavior of hiPSC‐osteoclasts indicated a trend towards forming more trenches than pits and an increase in pseudoresorption. We used hiPSCs from an autosomal recessive osteopetrosis (ARO) patient (BIHi002‐A, ARO hiPSCs) with compound heterozygous missense mutations p.(G292E) and p.(R403Q) in CLCN7, coding for the Cl − /H + ‐exchanger ClC‐7, for functional investigations. The patient's leading clinical feature was a brain malformation due to defective neuronal migration. Mutant ClC‐7 displayed residual expression and retained lysosomal co‐localization with OSTM1, the gene coding for the osteopetrosis‐associated transmembrane protein 1, but only ClC‐7 harboring the mutation p.(R403Q) gave strongly reduced ion currents. An increased autophagic flux in spite of unchanged lysosomal pH was evident in undifferentiated ARO hiPSCs. ARO hiPSC‐derived osteoclasts showed an increased size compared to hiPSCs of healthy donors. They were not able to resorb bone, underlining a loss‐of‐function effect of the mutations. In summary, we developed a highly reproducible, straightforward hiPSC‐osteoclast differentiation protocol. We demonstrated that osteoclasts differentiated from ARO hiPSCs can be used as a disease model for ARO and potentially also other osteoclast‐related diseases. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).